Is there creatine in plants? The true compound behind the 1H NMR signal at 3.05 ppm in plant extracts - Novais, Leice Milla Ribeiro de; Ali, Sher; D’Oca, Caroline Da Ros Montes; Salome, Kahlil Schwanka; Barison, Andersson (Frontiers in Natural Products, 2024)
Introduction Some papers describe the presence of creatine in plants, based on a singlet signal at 3.02–3.05 ppm in the 1H NMR spectra. Although is there creatine in plants? Therefore, to answer this question, a comprehensive NMR investigation has been performed aiming the unambiguous assignment of the compound responsible for that signal. Objective Determine whether the compound behind the signal at 3.05 ppm is truly creatine or if it was just a misassignment, instead. Methods Samples of leaves and cherries from Eugenia uniflora in their natural swollen state were submitted to HR-MAS NMR analysis. Results It was found that the signal at 3.05 ppm was misassigned to creatine. The exhaustive NMR investigation revealed that the signal is related to the amino acid 4-hydroxy-N-methyl proline, instead. Conclusion The comprehensive NMR investigation revealed that there is no creatine in plants, it was just a misassignment.